Layered co-continuous structure in bone scaffold fabricated by laser additive manufacturing for enhancing electro-responsive shape memory properties - Cijun Shuai; Wentao Xu; Haofan He; Feng Yang; Jinglin Liu; Pei Feng (Journal of Materials Research and Technology, 2024)
Porous scaffold based on electro-responsive shape memory polymers (ESMPs) possesses great potential applications in minimally invasive surgery for bone defect repair because it provides the ability for remote control and internal heating. However, it's difficult to obtain co-continuous structure in bone scaffold for achieving excellent electro-responsive shape memory properties. In this study, layered co-continuous structure with thermoplastic polyurethane (TPU) loaded with multi-walled carbon nanotubes (MWCNTs) (referred to as cTPU) layer and l-polylactic acid (PLLA) layer alternate stacking was obtained via layer-by-layer fabrication technology, and the porous scaffold was fabricated via selective laser sintering (SLS). The thermal and electrical shape memory properties of the scaffolds with different contents of MWCNT were evaluated by dynamic mechanical analysis (DMA) and U-bending experiments. The results indicated that the layered co-continuous structure improved phase continuity and confined MWCNTs to one side, enhancing the electrically driven properties and shape memory properties. The scaffold with 1.5 wt% MWCNTs achieved shape fixed and recovery rates of 95.6% and 90.2%, respectively. With the further increasing of MWCNTs content, the shape memory properties decreased due to the agglomeration of MWCNTs in the cTPU phase, which affected the phase continuity of cTPU. The DMA results confirmed the good mechanical properties of the scaffold, and the cell culture experiment results demonstrated excellent cytocompatibility for cell attachment and growth. This work provides a feasible method to fabricate electro-responsive shape memory bone scaffold with layered co-continuous structure, which exhibits great potential in applications of bone defect repair.